The Funeral rites of the Mongols in the perspective of trips: the tripe of John Plano Carpini (1245-1247) as model - Zubaidi, Abbas khamis (Al-Adab Journal, 2019)
The rites and practices of the pastoral tribes, concerning the dead were similar, since they shard the same life and climate, the same environment, blood and race to the extent that they were described by the travelers in different period alike. their rites ,however , remained unknown even for the Europeans till some Christian travelers visited that land and wrote important information in there memoirs .their visits were having religious and political aims especially after the Mongols had occupied many wide land whether relating to the Muslims or Christians , during the 13th century C.E / the 7th century A.H. The efforts of the Christian Nestorian and Latin missions had provided much information about the life of the Mongols .that life remained unknown foe west of Europe ,and thus, the implications of Mongols culture were not exactly examined ordiscovered deeply except via the papal trips, like the one related to pastor John Plano Carpini which left behind a valuable description about trips and the situations that were common among the Mongols Society in general , and palace in particular . Such information .however, can not be relied on completely as the legendary style seems clearly available within which reflected his culture and the ability of analyzing of what he saw or heard from their behaviors. The trips participated actually, in analyzing the behaviors and religious rites relating the Mongols as well as pointing there beliefs impressions about nature and its effect on life and death.